The Effects of Canal Blocking on Hydrological Restoration in Degraded Peat Swamp Forest Post-Forest Fires in Central Kalimantan - Suwito, D.; Suratman, Suratman; Poedjirahajoe, E. (Institute of Physics, 2022)
Tropical peat swamp forest is one of the wetland ecosystems on tropical peatlands with many ecological, economic, and socio-cultural functions. In Indonesia, the peat swamp forest ecosystems have been experiencing deforestation and degradation due to land clearing for plantations and agriculture and forest fires. In Central Kalimantan, especially in the ex-area of the 1 million hectares mega rice project (MRP)n in the 1990s, hydrological restoration is done by blocking the canals. We compared the three methods of canal blocking and the areas without canal blocking and the community's preference on what form of canal blocking is more beneficial for them. Large canal blocking, medium canal blocking, and small canal blocking had positively affected the groundwater level in the driest month above the fire-prone critical point. In contrast, the locations without blocking exceed the necessary fire-prone water level. Small, large, and medium blocking are equally capable of optimizing the peat soil water table. However, the local communities preferred small blocking over other methods because it was simple, labour-intensive, and improved their livelihood when involved in its construction. The local communities choose the big canal blockings less because they block transportation access in and out of the peat swamp forest. © Published under licence by IOP Publishing Ltd.